Untying the Agronomic Paradox of Weeding Yield Loss under Tropical Dew-fall Conditions - Moiwo, Juana Paul; Turay, Foday; Moiwo, Tuwoh Weiwoh; Allie, Georgiana (European Journal of Applied Sciences, 2026)
The foundational paradigm of weed science established through decades of agronomic research posits that weeds act as direct competitors to crops for essential resources, invariably causing significant yield suppression. This principle is particularly emphasized for groundnut (Arachis hypogaea L.), a vital legume for global food security, due to its slow initial growth. However, this universally accepted doctrine is challenged by emerging observations from specific agro-ecological niches characterized by pronounced tropical dew-fall, where unweeded groundnut plots have been observed to outperform the weeded counterparts. A field experiment was conducted using a Randomized Complete Block Design (RCBD) with three replications to investigate this anomaly. Treatments consisted of a weeded control (W), manually weeded at 45 Days After Planting (DAP), and an unweeded treatment (UW). The results clearly validated the yield anomaly. The unweeded treatment demonstrated 44.9% higher final dry pod yield (150.41 g/plot) compared to the weeded control (103.84 g/plot), translating to 30.96% yield loss attributable to weeding. Unweeded plots also produced 21.5% more pods per plant and 31.7% higher fresh plant biomass. Early growth stages showed no competitive suppression. These findings robustly confirmed that the net effect of weed community in this environment was profoundly facilitative. The results were interpreted as strong evidence for a proposed mechanism where weed understorey enhanced dew capture and retention, and the groundnut crop utilized this supplementary moisture via foliar water uptake. That led to improved water status and photosynthetic efficiency that overwhelmingly offset the costs of below-ground competition. It was concluded that the universal agronomic paradigm that mandates routine weeding for groundnut was not applicable in tropical dew-fall environments and a paradigm shift therefore recommended towards context-specific management that leverages beneficial ecological interactions.